2016
DOI: 10.1063/1.4964905
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of coherent rotating modes in a magnetised plasma column using a mono-sensor tomography diagnostic

Abstract: . Characterisation of coherent rotating modes in a magnetised plasma column using a mono-sensor tomography diagnostic. 2016. Characterisation of coherent rotating modes in a magnetised plasma column using a mono-sensor tomography diagnostic In this paper we report on an original tomographic diagnostic using a single sensor on a magnetized plasma column. The experimental set-up and the numerical inversion method used to interpret the data are presented. The core plasma evolution during the rotatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…It was observed that by modifying the source potential, the mode could be transitioned from an m=2, to m=1 to a purely turbulent spectrum 14 . The low mode number structures were correlated strongly with anomalous transport 15 , and tomography measurements showed that the structure roughly retained its shape throughout rotation 16 . Further work has been carried out within a Penning discharge at the Princeton Plasma Physics Laboratory (PPPL).…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…It was observed that by modifying the source potential, the mode could be transitioned from an m=2, to m=1 to a purely turbulent spectrum 14 . The low mode number structures were correlated strongly with anomalous transport 15 , and tomography measurements showed that the structure roughly retained its shape throughout rotation 16 . Further work has been carried out within a Penning discharge at the Princeton Plasma Physics Laboratory (PPPL).…”
mentioning
confidence: 87%
“…The preferential diffusion of the weakly magnetized ions results in a radial ambipolar field and therefore ExB drifts in the azimuthal direction. The Penning discharge has similar plasma parameters, electric and magnetic fields as the near-anode region of a Hall thruster, where a spoke-like coherent structure is commonly observed 12,13,14,15,16 . Penning discharges provide more convenient access for diagnostics than Hall thrusters do, and the physics is somewhat simplified by the lack of a magnetic field gradient, eliminating one energy source able to drive instabilities 17 .…”
mentioning
confidence: 99%
“…In this work, a visible spectro-tomographic diagnostic installed on the Mistral experiment is presented. It is an update of a previous tomographic setup [14,17]. In the present case 49 optical fibres, divided in two fans, collect the plasma emission and send it to an imaging spectrometer, giving a simultaneous access to the brightness of emission lines in the whole visible and the near IR argon spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…In the present case 49 optical fibres, divided in two fans, collect the plasma emission and send it to an imaging spectrometer, giving a simultaneous access to the brightness of emission lines in the whole visible and the near IR argon spectrum. Specifically developed software operates the tomographic reconstruction [14,17], leading to 7 x 7 pixels plasma images, with 16 mm square pixels.…”
Section: Discussionmentioning
confidence: 99%
“…1 is used for the fundamental study of transport in cold plasmas (T e ∼ 3 eV and T i ∼ 300 K). [2][3][4][5][6][7] . An Argon plasma is created by a thermoionic discharge, with a typical pressure P ≃ 10 −2 Pa and electron density n e ≃ 10 −15 m −3 .…”
Section: Introductionmentioning
confidence: 99%